PERBEDAAN PENAMBAHAN BERAT BADAN PADA AKSEPTOR KONTRASEPSI SUNTIK 3 BULAN DENGAN 1 BULAN DI KELURAHAN KARANG KIDUL KECAMATAN MAGELANG SELATAN KOTA MAGELANG - Atania Rachma; Sri Widatiningsih (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2016)
Injected contraception is the most contraception method chosen by Indonesian women. There are 2 types of injected contraception, 3 monthly injecion which consists of progesterone only and 1 monthly injection consists of a combination of oesterogen-progesterone. One of its side effect is body weight gain, which is usually distressing for women due to the increase risk of suffering from many diseases such as heart attack, type-2 diabetes mellitus, sleep apnea, certain cancer, osteoarthritis, and asthma.The study aim was to identify the difference weight gain occurence between 3 monthly and 1 monthly injected contraception users in Karang Kidul Village- South Magelang District. Sample size were 46 respondents for 3 monthly injection and 46 respondents for 1 monthly injection. Case control design were applied and Mann-Whitneystatistical test were used with p value of 0.05 were applied.The result showed a ρ value of 0,00 which meant there was a difference in weight gain occurence between the users of 3 monthly and 1 monthly injected contraception. The 3 monthly injection had been proven increasing the incidence of weight gain compared to the 1 monthly one.It was suggested that midwives should give proper counselling regarding to side effect of increasing weight gain during the use of 3 monthly contraceptive injection to be aware of by the users. Further investigation on other influencing factors of weight gain among contraceptive injection users.